Question
upstudy study bank question image url

1) \( \begin{aligned}(2 x+3)(5 x+1) & =0 \\ \text { 1) }(x-3)(x+9) & =0\end{aligned} \)

Ask by Simpson Beck. in South Africa
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are: - For (2x + 3)(5x + 1) = 0: x = -3/2 or x = -1/5 - For (x - 3)(x + 9) = 0: x = 3 or x = -9

Solution

Let's solve each equation step by step: ────────────────────────────── Equation 1: (2x + 3)(5x + 1) = 0 Using the zero product property, set each factor equal to zero: 1. 2x + 3 = 0   Subtract 3: 2x = -3   Divide by 2: x = -3/2 2. 5x + 1 = 0   Subtract 1: 5x = -1   Divide by 5: x = -1/5 So, the solutions for the first equation are x = -3/2 and x = -1/5. ────────────────────────────── Equation 2: (x - 3)(x + 9) = 0 Again, apply the zero product property: 1. x - 3 = 0   Add 3: x = 3 2. x + 9 = 0   Subtract 9: x = -9 Thus, the solutions for the second equation are x = 3 and x = -9. ────────────────────────────── Summary of Solutions: • For (2x + 3)(5x + 1) = 0:   x = -3/2 or x = -1/5 • For (x - 3)(x + 9) = 0:   x = 3 or x = -9

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the first equation \( (2x + 3)(5x + 1) = 0 \), we set each factor to zero. This gives us \( 2x + 3 = 0 \) leading to \( x = -\frac{3}{2} \), and \( 5x + 1 = 0 \) giving \( x = -\frac{1}{5} \). For the second equation \( (x - 3)(x + 9) = 0 \), we set each factor equal to zero as well. This results in \( x - 3 = 0 \) which gives \( x = 3 \), and \( x + 9 = 0 \) leading to \( x = -9 \). Now you have four distinct solutions: \( x = -\frac{3}{2}, -\frac{1}{5}, 3, \) and \( -9 \)!

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy